2003
DOI: 10.1002/ijc.11225
|View full text |Cite
|
Sign up to set email alerts
|

The deregulation of arachidonic acid metabolism‐related genes in human esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is 1 of the most common cancers worldwide. In our study, cDNA microarray comprising 14,803 genes was employed to identify gene-specific expression profile in 6 paired samples of ESCC. Nine genes identified were commonly upregulated and 36 downregulated in tumors, as compared to normal esophageal squamous epithelia. Among these genes, we found that 9 of the altered expression genes were related to arachidonic acid (AA) metabolism, such as annexin-I, annexin-II, S100A8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 34 publications
2
63
0
1
Order By: Relevance
“…Upregulation of ANX2 expression has been reported in hepatocellular carcinoma (Frohlich et al, 1990), lung cancer (Cole et al, 1992), pancreatic cancer (Diaz et al, 2004;Esposito et al, 2006), breast cancer (Sharma et al, 2006), gastrointestinal cancer (Singh, 2007), glioma (Reeves et al, 1992) and colorectal cancer (Emoto et al, 2001b). Conversely, downregulation of ANX2 expression has been reported in prostate cancer (Chetcuti et al, 2001;Banerjee et al, 2003;Liu et al, 2003), osteosarcoma (Gillette et al, 2004), oesophageal squamous cell carcinoma (SCC) (Zhi et al, 2003) and head and neck SCC (Pena-Alonso et al, 2008). This discrepancy may be explained by ANX2 expression in the histological origin of tumours, the cellular localisation and the putative function of ANX2 in tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ANX2 expression has been reported in hepatocellular carcinoma (Frohlich et al, 1990), lung cancer (Cole et al, 1992), pancreatic cancer (Diaz et al, 2004;Esposito et al, 2006), breast cancer (Sharma et al, 2006), gastrointestinal cancer (Singh, 2007), glioma (Reeves et al, 1992) and colorectal cancer (Emoto et al, 2001b). Conversely, downregulation of ANX2 expression has been reported in prostate cancer (Chetcuti et al, 2001;Banerjee et al, 2003;Liu et al, 2003), osteosarcoma (Gillette et al, 2004), oesophageal squamous cell carcinoma (SCC) (Zhi et al, 2003) and head and neck SCC (Pena-Alonso et al, 2008). This discrepancy may be explained by ANX2 expression in the histological origin of tumours, the cellular localisation and the putative function of ANX2 in tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic approaches using microarray-based global transcriptome analysis might provide a powerful alternative with an unprecedented view scope in monitoring gene expression levels [9] . By analyzing our cDNA microarray data, we have recently identified MRP8 and MRP14 as two down-regulated and differentiation-associated genes in a significant proportion of ESCCs [10,11] . Myeloid-related protein 8 (MRP8; S100A8) and MRP14 (S100A9) are two calcium-binding proteins belonging to the S100 family [12] .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, many esophageal cancer deregulated genes showed differential expression during mice embryonic development. These genes covered a broad spectrum of biologic functions including cell proliferation (RPL15) [10,11] , differentiation (S100A8 [5] , SPRR2A [12] ), immune response (IGL) [13] , cytoskeletal protein (TUBA1) [14] migration (cystatin B) [15] , etc. These findings provided further clues to the possible function of these deregulated genes and the tumorigenesis of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA microarray technology allows simultaneous determination of the expression level of thousands of genes [3] . Up to date, by using the cDNA array technology, we have identified many genes differentially expressed in esophageal cancer, which potentially play key roles in the malignant behavior of esophagus [4,5] . Investigation into the biological function of these genes could be helpful to understand the molecular mechanisms in tumorigenesis of ESCC.…”
Section: Introductionmentioning
confidence: 99%